The hidden half of nature : the microbial roots of life and health - Montgomery, David R., 1961-; Biklé, Anne (W.W. Norton & Company, 2016)
"Prepare to set aside what you think you know about yourself and microbes. Good health--for people and for plants--depends on Earth's smallest creatures. [This book] tells the story of our tangled relationship with microbes and their potential to revolutionize agriculture and medicine, from garden to gut"--Dust jacket flap.